Confused and tetraplegic: examine your ICU patient. Issue 6 (27th May 2022) - Aslanyan, Aram; Herwadkar, Amit; Sharaf, Nazar; Jones, Matthew; Kobylecki, Christopher; Lavin, Tim; Cahill, Varduhi
Abstract : Introduction: Glial Fibrillary Acidic Protein (GFAP) astrocytopathy can manifest as a combination of meningitis, encephalitis or myelitis syndrome, which makes the diagnosis challenging, especially in the Intensive Care setting. Case Presentation: We present a case of 43-year-old male who presented to ED with headache, fever, myalgia and acute confusion complicated by respiratory failure attributed to aspiration pneumonia in need of ventilatory support. CSF findings were remarkable for lymphocytic pleocytosis (WCC 197, 95% lymphocytes) and markedly elevated protein of 3.52g/L resulting in the diagnosis of meningoencephalitis. Following a sedation hold he was found to have flaccid quadriparesis and a truncal sensory level, which was not present on admission. An MRI brain showed linear perivascular radial enhancement while the cervicothoracic spine showed longitudinally extensive transverse myelitis. Extensive investigations rendered positive CSF GFAP antibodies. The patient was treated with intravenous Methylprednisolone and plasma exchange followed by a tapering dose of oral steroids. Upon his discharge to a rehabilitation facility the patient was a manual wheelchair user. Discussion: This case demonstrates the importance of a thorough assessment of ICU patients for the timely detection of an evolving neurological deficit. A high index of suspicion for GFAP-mediated inflammation is warranted in patients presenting with meningoencephalomyelitis. aram.aslanyan@srft.nhs.uk